Improving agricultural sustainability in Bosnia and Herzegovina through renewable energy integration - Adis Puška; Miroslav Nedeljković; Branislav Dudić; Anelka Štilić; Alexandra Mittelman (Economies, 2024)
With the development of agricultural production, the demand for electricity correspondingly increases. To sustainably meet this demand, renewable energy sources (RESs) can be utilized. This paper explores the application of RES alternatives in agriculture to provide guidelines for enhancing sustainable agricultural practices in Bosnia and Herzegovina. The study employs expert decision making using fuzzy multi-criteria decision-making (MCDM) methods. A decision-making model incorporating nine criteria and six alternatives was developed. Using the direct weight calculation (DiWeC) approach, the findings indicate that economic criteria are prioritized over other sustainability criteria. The results from the fuzzy RAWEC (ranking of alternatives with weights of criteria) method reveal that solar energy has the greatest potential for advancing sustainable agricultural production in Bosnia and Herzegovina. For practical implementation of RES alternatives, active involvement from state institutions and local communities is essential.
Keywords: 330; agricultural production; Bosnia and Herzegovina; enhancing sustainable agriculture; fuzzy logic; renewable energy; sustainable energy sources